The Effect of Lockdown During the Covid-19 Pandemic on Bird Species Richness at IPB Dramaga Campus - Hidayat, Haris Akbar; Dewanti, Anindya; Tirtaningtyas, Fransisca; Mulyani, Yeni Aryati (Jurnal Sumberdaya Hayati, 2024)
IPB Dramaga Campus in Bogor has been recognized to hold a high diversity of birds, while at the same time is also experiencing disturbance due to human activities. During the covid-19 pandemic in 2020-early 2022, most human activities on campus were decreased. Observations made during lockdown indicated that birds were seen more easily in various habitats on campus. The objective of this study was to describe bird species richness and composition before the period of lockdown and after the pandemic (post-lockdown). Bird surveys were conducted monthly in 2019 and from January to May 2023 to obtain a bird species list. Mist nets were set up monthly for 3 months in 2019 and 2023 to obtain demographic data. Descriptive analysis was conducted by comparing the results with previous data collected by Uni Konservasi Fauna (UKF) and Cikabayan Bird Banding Club (CBC). The number of bird species between the two periods did not differ significantly; there were 66 species in while in 2023 there were 60 species. In both periods bird species composition was dominated by the family of Cuculidae, and the dominant feeding guild was insectivores.